Ginsenoside Rb1 enhances atherosclerotic plaque stability by skewing macrophages to the M2 phenotype. Issue 1 (25th September 2017) - Zhang, Xue; Liu, Ming‐hao; Qiao, Lei; Zhang, Xin‐yu; Liu, Xiao‐ling; Dong, Mei; Dai, Hong‐yan; Ni, Mei; Luan, Xiao‐rong; Guan, Jun; Lu, Hui‐xia
Abstract: Atherosclerosis (AS) is characterized as progressive arterial plaque, which is easy to rupture under low stability. Macrophage polarization and inflammation response plays an important role in regulating plaque stability. Ginsenoside Rb1 (Rb1), one of the main active principles of Panax Ginseng, has been found powerful potential in alleviating inflammatory response. However, whether Rb1 could exert protective effects on AS plaque stability remains unclear. This study investigated the role of Rb1 on macrophage polarization and atherosclerotic plaque stability using primary peritoneal macrophages isolated from C57BL/6 mice and AS model in ApoE −/− mice. In vitro, Rb1 treatment promoted the expression of arginase‐I (Arg‐I) and macrophage mannose receptor (CD206), two classic M2 macrophages markers, while the expression of iNOS (M1 macrophages) was decreased. Rb1 increased interleukin‐4 (IL‐4) and interleukin‐13 (IL‐13) secretion in supernatant and promoted STAT6 phosphorylation. IL‐4 and/or IL‐13 neutralizing antibodies and leflunomide, a STAT6 inhibitor attenuated the up‐regulation of M2 markers induced by Rb1. In vivo, the administration of Rb1 promoted atherosclerotic lesion stability, accompanied by increased M2 macrophage phenotype and reduced MMP‐9 staining. These data suggested that Rb1 enhanced atherosclerotic plaque stability through promoting anti‐inflammatory M2 macrophage polarization, which is achieved partly by increasing the production of IL‐4 and/or IL‐13 and STAT6 phosphorylation. Our study provides new evidence for possibility of Rb1 in prevention and treatment of atherosclerosis.